Expression and Characterization of an Alginate Lyase and Its Thermostable Mutant in Pichia pastoris - Yang, Suxiao (Mar Drugs, 2020)
Alginate is one of the most abundant polysaccharides in algae. Alginate lyase degrades alginate through a β-elimination mechanism to produce alginate oligosaccharides with special bioactivities. Improving enzyme activity and thermal stability can promote the application of alginate lyase in the industrial preparation of alginate oligosaccharides. In this study, the recombinant alginate lyase cAlyM and its thermostable mutant 102C300C were expressed and characterized in Pichia pastoris. The specific activities of cAlyM and 102C300C were 277.1 U/mg and 249.6 U/mg, respectively. Both enzymes showed maximal activity at 50 °C and pH 8.0 and polyG preference. The half-life values of 102C300C at 45 °C and 50 °C were 2.6 times and 11.7 times the values of cAlyM, respectively. The degradation products of 102C300C with a lower degree of polymerization contained more guluronate. The oligosaccharides with a polymerization degree of 2–4 were the final hydrolytic products. Therefore, 102C300C is potentially valuable in the production of alginate oligosaccharides with specific M/G ratio and molecular weights.